lncRNA Signature for Predicting Cerebral Vasospasm in Patients with SAH: Implications for Precision Neurosurgery - Chen-Yu Pan; Miao Tian; Lei-Lei Zhang; Dan Tian; Li-Yan Wang; Yu-Jia Sun; Yun-Feng Cui (Elsevier, 2020)
Subarachnoid hemorrhage (SAH) patients' surgery is performed to prevent extravasation of blood into the subarachnoid space. Cerebral vasospasm (CVS; narrowing of cerebral arteries) occurs following SAH and represents a major cause of associated mortality and morbidity. To improve postsurgery care of SAH patients and their prognosis, the ability to predict CVS onset is critical. We report a long noncoding RNA (lncRNA) signature to distinguish SAH patients with CVS from SAH patients without CVS. Cerebrospinal fluid (CSF) was obtained from SAH patients without CVS (n = 10) and SAH patients with CVS (n = 10). lncRNAs ZFAS1 and MALAT1 were significantly upregulated (p < 0.05), whereas lncRNAs LINC00261 and LINC01619 were significantly downregulated in SAH patients with CVS (p < 0.05) compared to SAH patients without CVS. We applied this lncRNA signature to retrospectively predict CVS in SAH patients (n = 38 for SAH patients without CVS, and n = 27 for SAH patients with CVS). The 4-lncRNA signature was found to be predictive in >40% of samples and the 2-lncRNA comprising MALAT1 and LINC01619 accurately predicted CVS in ∼90% cases. These results are initial steps toward personalized management of SAH patients in clinics and provide novel CSF biomarkers that can substantially improve the clinical management of SAH patients.